The Analysis of Public Satisfaction Survey Implementation in The Representative Board of Central Java Province - Indriastuti, Menuk; Veithzal Rivai Zainal; Aziz Hakim (Dinasti International Journal of Digital Business Management, 2023)
Measurement of public satisfaction index is an attempt to determine organizational performance in the service of government institutions which is carried out periodically and it can be used as material for organizational policies in improving the quality of their own public services. The aim of this paper is to analyze the level of customer satisfaction, knowing the elements that must be improved and how to increase public satisfaction. The Public Satisfaction Index by In Regulation of Ministry of State Apparatus Utilization and Bureaucratic Reform No. 14 of 2017 is Requirements, Systems and Infrastructure as well as Complaint Handling, suggestions and input. Based on the indicators for measuring public satisfaction at the Representative Board for Central Java Province, the authors recommend the following: (1) adjustments to Guest house roomrates and (2) optimal publication on social media of Representative Board for Central Java Province.